Elimination disorders and associated factors among children and adolescents age 5-14 year-old attending paediatric outpatient clinic at Wolaita Sodo University comprehensive specialized hospital, South Ethiopia - Tamene Berhanu; Mubarek Abera; Shimelis Girma; Yonas Tesfaye (BMC, 2024)
Abstract Background Elimination disorder occurs in children over the age of normal toileting who continue to have an inability to control urination or feces, either during the day, at night, or both. Paediatric elimination disorders are not well understood by parents, teachers, medical professionals, mental health practitioners, and researchers. Hence, this study aimed to assess the magnitude of elimination disorder and associated factors among children and Adolescents aged 5-14 years old at Wolaita Sodo University Comprehensive Specialized Hospital, South Ethiopia, in 2022. Method A hospital-based cross-sectional study was conducted from September 22 to November 22, 2022, at Wolaita Sodo University Comprehensive Specialized Hospital. A systematic random sampling technique was employed to select 423 study subjects. The data were gathered using a structured, face-to-face interviewer-administered questionnaire. The development of the symptom score for dysfunctional elimination syndrome of Vancouver questionnaires was used to screen for elimination disorders. Logistic regression model was used to determine the association between the outcome and independent variables. A 95% CI and Odds ratio with corresponding p-value < 0.05 were used to determine the predictors of the outcome variable. Result The overall magnitude of elimination disorder among children and Adolescents age 5-14 in this study was (n 70, 16.8%); in boys (n 47, 17.3%) and girls (n 23, 15.75%). The prevalence of enuresis was (n 64, 15.3%), encopresis (n 15, 3.6%), both enuresis and encopresis, or combined elimination disorder (n 9, 2.2%). Age 9-11 years (AOR = 3.2, 95%CI:1.09, 9.43), family size four and above (AOR = 3.4, 95%CI:1.78, 6.56), family history of elimination disorder (AOR = 3.9, 95%CI:2.12, 7.45), emotional problem (AOR = 2.2, 95%CI:1.18, 4.05), hyperactive problem (AOR = 3.8, 95%CI:1.83, 7.83), low toilet training skills (AOR = 5.9, 95%CI:2.61, 13.33), bad parenting practices, were poor supervision (AOR = 4.4, 95%CI 1.29, 14.69) were significantly associated with elimination disorder. Conclusion and recommendation In this study, approximately one in five children and adolescents had an elimination disorder. Younger age, family size four and above, positive family history of elimination disorder, presence of emotional and hyperactive problems, bad parenting practices, and low toilet training skills were factors associated with elimination disorders. Therefore, preventative, etiological, and therapeutic measure, early toilet training, supportive parenting practices, screening for children's and adolescents' behavioral problems, and elimination disorders need attention to reduce the effect of the problem.